2021
DOI: 10.1088/1755-1315/904/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Potassium and Cytokinins in the Vegetative Growth Traits of Faba Bean (Vicia faba L.)

Abstract: A field experiment was carried out at the Al-Hsai District/Falluja City/Al-Anbar Province during the winter season 2020-2021. To study the effect of Nano potassium (NK) and Cytokinin (CTK) on the growth, and quality of the local cultivar of faba bean. Split plot system was used according to the design of a completely randomized block design R.C.B.D and three replications. The main blocks included four concentrations of CTK; 0, 50, 100, and 150 mg. L-1, while the secondary blocks included four concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
3
0
0
Order By: Relevance
“…The reason may be due to the superiority of the Lee cultivar in this trait due to the nature of the genetic of the cultivars, which was clearly reflected in their response to environmental conditions, and thus increased cell division and elongation, which positively affected the increase in plant height. The result was in line with what was found by some researchers [7,15], who found that soybean cultivars differed among themselves in plant height. Effect of spraying the growth regulator TRIA on plant height directly proportional with increasing the concentration of the growth regulator.…”
Section: Plant Height (Cm)supporting
confidence: 93%
See 2 more Smart Citations
“…The reason may be due to the superiority of the Lee cultivar in this trait due to the nature of the genetic of the cultivars, which was clearly reflected in their response to environmental conditions, and thus increased cell division and elongation, which positively affected the increase in plant height. The result was in line with what was found by some researchers [7,15], who found that soybean cultivars differed among themselves in plant height. Effect of spraying the growth regulator TRIA on plant height directly proportional with increasing the concentration of the growth regulator.…”
Section: Plant Height (Cm)supporting
confidence: 93%
“…The spraying of plants with a concentration of 40 mg L -1 achieved the highest average of 38.71 SPAD for the studied trait, and it did not differ significantly from the plants sprayed with a concentration of 50 mg L -1 , which achieved an average of 37.84 SPAD, while these averages decreased when the plants were treated with distilled water (control treatment) with the lowest mean of 33.64 SPAD. The results were in line with what was found [14,15]. The results showed a significant interaction study factor, the results showed that spraying the plants of Se-220 cultivar with the growth regulator TRIA at a concentration of 40 mg L -1 gave the highest average for this trait amounted to 40.87 SPAD, while the plants of the same cultivar when sprayed with distilled water only recorded the lowest average of 32.33 SPAD.…”
Section: Chlorophyll Index (Spad)supporting
confidence: 89%
See 1 more Smart Citation